History of colonization of the Kazakh steppe in written sources of the 19th century: electronic collection - Alzhanova, E.E.; Kasymbekov, A.S. (Publ.KarSU, 2018)
Questions of creation of an electronic collection of information resources on history of colonization of the Kazakh steppe in written sources of the 19th century for formation of electronic catalogs and full text databases are considered in this article. During the creation of an electronic collection of information resources on history of colonization of the Kazakh steppe in written sources of the 19th century there were used more than 100 sources of information materials – original historical documents and photos of the Turkestan collection. The created electronic collection of information resources on history of colonization of the Kazakh steppe contains information materials from the Turkestan collection which were carefully analysed and systematized on subject in written sources of the 19th century and are presented as the separate PDF files. The electronic collection is formed on the basis of modern information technologies that will allow to increase the level of scientific and educational researches and to organize effective work of quick search, the analysis, systematization and storage of information resources.
XIX ғасыр жазба дереккөздеріндегі Қазақ даласын отарлау саясатының тарихы: электрондық жиынтық
История колонизации Казахской степи в письменных источниках XIX века: электронная коллекция
Keywords: electronic collection; electronic catalog and database; electronic library; information resources; full text documents; colonization of the Kazakh steppe; written sources of the 19th century